Vaginal Birth after Cesarean Section: Provider Perspectives and Maternal Decision Making - Isabella Chan; Emily Bronson; Allison Cantor (University of North Florida, 2015)
Although evidence suggests vaginal birth after cesarean section (VBAC) leads to fewer complications in subsequent pregnancies, lower risk of maternal morbidity, and fewer cesarean sections overall, VBAC rates in Florida are at 5.5%, notably lower than the U.S. average of 8.0%. This exploratory study examines the factors contributing to these low VBAC rates through a qualitative investigation using grounded theory. Semi-structured interviews with women and maternity care providers were conducted to explore attitudes, motivations, and experiences regarding VBAC. Findings reveal a distinction between providers' and women's attitudes toward and experiences with VBAC and identify factors involved in decision-making. Three themes emerged: (1) patient-provider interactions; (2) perceptions of risks; and (3) rejection/adoption of biomedical authority. Women weighed the risks and benefits of VBAC through their perceptions and experiences of physical and emotional consequences, whereas providers relied on their experiences with medical practice, legal outcomes, policy, and evidence-based medicine. This exploratory research identifies a critical need for further attention to the disconnects between providers' and women's perspectives on and experiences with VBAC to address the tensions between biomedical and alternative forms of birth knowledge better and develop comprehensive VBAC guidelines that integrate the needs and concerns of women and providers.